A simple, sensitive, and straightforward LC–MS approach for rapid analysis of three potential genotoxic impurities in rabeprazole formulations. Issue 21 (10th September 2018) - Yenugu, Veera Manohara Reddy; Ambavaram, Vijaya Bhaskar Reddy; Moniruzzaman, Muhammad; Madhavi, Gajulapalle
Abstract: In the present study, a sensitive and fully validated liquid chromatography with mass spectrometry method was developed for the quantification of three potential genotoxic impurities in rabeprazole drug substance. The separation was achieved on Symmetry C18 column (100 × 4.6 mm, 3.5 μm) using 0.1% formic acid in water as mobile phase A and acetonitrile as mobile phase B in gradient elution mode at 0.5 mL/min flow rate. Triple quadrupole mass detection with electrospray ionization was operated in selected ion recording mode for the quantification of impurities. The calibration curves were demonstrated good linearity over the concentration range of 1.0–4.5 ppm for O ‐phenylenediamine, 1.8–4.5 ppm for 4‐nitrolutidine‐ N ‐oxide and 1.0–4.5 ppm for benzyltriethylammonium chloride with respect to 10 mg/mL of rabeprazole. The correlation coefficient obtained in each case was >0.998. The recoveries were found satisfactory over the range between 94.22 and 106.84% for all selected impurities. The method validation was carried out following International Conference on Harmonization guidelines, from which the developed method was able to quantitate the impurities at 1.0 ppm for O ‐phenylenediamine, 1.8 ppm for 4‐nitrolutidine‐ N ‐oxide and 1.0 ppm for benzyltriethylammonium chloride. Furthermore, the proposed method was successfully evaluated for the determination of selected impurities from bulk drug and formulation samples of rabeprazole within the acceptable limits.